A polymer sealing reinforced filler tape and preparation method thereof
By designing a sealant layer and active surface layer containing imidazolyl polyurethane and modified carbon nanotubes in the sealing tape, the problem of the existing sealing reinforcement filler tape failing in fire or flammable conditions is solved, and good flame retardant is achieved. Antibacterial and bonding effects.
Patent Information
- Application Number
- CN202411766908.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing sealing reinforcement filler tape is prone to failure in fire or flammable conditions, affecting its normal use, and lacks flame retardant and antibacterial effects.
A polymer sealing reinforced filler tape is used, which includes a sealing adhesive layer and an active surface layer. The sealant layer consists of butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium borate tackifier, zinc oxide and imidazole polyurethane, and the active surface layer contains tallow-based primary amine Corrosion inhibitor, citric acid, glycerin, sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin and modified carbon nanotubes.
The polymer sealing reinforced filler tape has good flame retardant, antibacterial and adhesive effects, and can maintain sealing performance in fire or flammable conditions, and is not easy to burn.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, in particular to a polymer sealing and reinforcing filler adhesive tape and a preparation method thereof. Background Art
[0002] Sealing reinforcement filler tape is a polymer material used to enhance the sealing effect. It plays an important role in many industrial fields, especially in application scenarios that require high reliability and long-term durability. However, it is flammable and can affect its normal use in the event of a fire during use. How to avoid this phenomenon is the key to solving the problem. For example, patent CN118772833A discloses a method for preparing a silicone structural sealant. The invention also adds hexadecyl phosphate and lauric acid to modify nano-calcium carbonate, which effectively increases its hydrophobicity. The modified nano-calcium carbonate is used in the preparation of sealants, which can greatly increase the waterproof performance of the finished sealant; however, its flame retardant and antibacterial effects are not improved. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In order to solve the problems raised in the background technology, the present invention provides a polymer sealing reinforcement filler tape and a preparation method thereof, which has good flame retardant, antibacterial and bonding effects.
[0005] (II) Technical solution
[0006] To achieve the above object, the present invention provides the following technical scheme: a polymer sealing reinforcing filler tape, comprising a sealing rubber layer and an active surface layer; the sealing rubber layer is composed of the following components by weight: 45-60 parts by weight of butyl rubber, 5-10 parts by weight of terpene resin, 3-5 parts by weight of low-density polyethylene, 4-6 parts by weight of white carbon black, 5-8 parts by weight of trieugenol quaternary ammonium salt borate tackifier, 2-4 parts by weight of zinc oxide, and 3-5 parts by weight of imidazole polyurethane;
[0007] The active surface layer comprises the following components in parts by weight: 1-2 parts by weight of a tallow primary amine corrosion inhibitor, 2-5 parts by weight of citric acid, 15-20 parts by weight of glycerol, 3-8 parts by weight of a sodium dodecyl sulfate surfactant, 25-40 parts by weight of bisphenol A type E51 epoxy resin, and 4-8 parts by weight of modified carbon nanotubes.
[0008] Furthermore, the preparation method of the imidazole-based polyurethane is:
[0009] (1) Add 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 2-aminoethanethiol to ethanol, heat to 25-40°C and react for 6-10 hours, then add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 50-75°C for 1-3 hours. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1;
[0010] (2) Add magnolol to N,N-dimethylformamide solvent, stir and disperse, then add intermediate 1 and benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 35-50° C. for 2-4 hours, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0011] (3) Add 4-hydroxyethylimidazole and L-lysine to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfone catalyst, react at 75-90°C for 4-7h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0012] (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst dropwise, react at 65-80°C for 2-5 hours to carry out prepolymerization, then add a triazine-based chain extender and an imidazole-based chain extender, stir to continue the chain extension reaction, react at 50-70°C for 4-6 hours, and after the reaction is completed, cool and discharge the material to obtain an imidazole-based polyurethane.
[0013] In the above reaction process, the aldehyde group in 2,4,6-tris(4-formylphenyl)-1,3,5-triazine reacts with the amino group in 2-aminoethanethiol, and then continues to react with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to introduce a thiol group, thereby obtaining an intermediate 1; the alkenyl group in magnolol and the thiol group of the intermediate 1 undergo a click reaction to introduce a phenolic hydroxyl group, thereby obtaining a triazine-based chain extender; the hydroxyl group in 4-hydroxyethylimidazole reacts with the carboxyl group in L-lysine to introduce an amino group, thereby obtaining an imidazole-based chain extender; the polyether diol is dehydrated and mixed evenly with hexamethylene diisocyanate, and then a dibutyltin dilaurate catalyst is added dropwise to perform a prepolymerization reaction, and then a triazine-based chain extender and an imidazole-based chain extender are added, and the chain extension reaction is continued by stirring to obtain an imidazole-based polyurethane.
[0014] Furthermore, in (1), the mass ratio of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine, 2-aminoethanethiol, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:3.1-3.6:2.4-2.8.
[0015] Furthermore, the mass ratio of magnolol, intermediate 1, and benzoin dimethyl ether photoinitiator in (2) is 0.8-1.1:1:0.01-0.03.
[0016] Furthermore, in said (3), the mass ratio of 4-hydroxyethylimidazole, L-lysine and p-toluenesulfone catalyst is 1:1.1-1.25:0.02-0.03.
[0017] Furthermore, in the (4), the mass ratio of the polyether diol after dehydration, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, triazine-based chain extender, and imidazole-based chain extender is 1.3-1.5:1:0.01-0.02:0.4-0.5:0.2-0.6.
[0018] Furthermore, the preparation method of the modified carbon nanotubes is as follows: 2-5g of carbon nanotubes are added to a mixed acid solution for acidification, wherein the mixed acid solution is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 3-4g of the acidified carbon nanotubes are added to N,N-dimethylacetamide, ultrasonically dispersed, and 6-12g of an imidazole chain extender, 7-9g of acyl chloride silane and 0.4-0.6g of a pyridine catalyst are added thereto, reacted at 60-80°C for 9-11h, centrifuged after the reaction, washed with acetone, and dried to obtain the modified carbon nanotubes.
[0019] Furthermore, the preparation method of the polymer sealing reinforcement filler tape is:
[0020] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane into a rubber mixer and mix them evenly. Mix them at a temperature of 60-100°C for 1-1.5 hours under a vacuum condition of -0.05 to -0.1 MPa, and naturally cool to room temperature to obtain a sealant layer.
[0021] S2. The tallow primary amine corrosion inhibitor, citric acid, glycerol, sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.5-1h and allowed to stand for 5-7min to obtain an active surface layer;
[0022] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, with a thickness of 0.9-1.1 mm;
[0023] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.4-0.6mm;
[0024] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.3-0.5 mm;
[0025] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0026] 3. Beneficial technical effects:
[0027] The polymer sealing and strengthening filler tape of the present invention comprises a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole-based polyurethane; the active surface layer comprises the following components by weight: a tallow-based primary amine corrosion inhibitor, citric acid, glycerol, a sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes.
[0028] The imidazole groups in the imidazole-based polyurethane and modified carbon nanotubes have good antibacterial effects. The imidazole groups can interact with the phospholipid bilayer on the bacterial cell membrane, causing changes in the structure of the cell membrane, thereby affecting its function and achieving an antibacterial effect. The triazine groups, sulfur elements, phosphorus elements, and carbon nanotube structures in the imidazole-based polyurethane and modified carbon nanotubes all have good flame retardant effects, forming a flame retardant system together, and synergistic flame retardancy. The imidazole groups in the imidazole-based polyurethane and modified carbon nanotubes will cure with the epoxy groups in the bisphenol A type E51 epoxy resin, and the dual curing further improves its bonding strength. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A polymer sealing and reinforcing filler tape, comprising a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: 45g of butyl rubber, 5g of terpene resin, 3g of low-density polyethylene, 4g of white carbon black, 5g of trieugenol quaternary ammonium salt borate tackifier, 2g of zinc oxide, and 3g of imidazole-based polyurethane;
[0032] The active surface layer comprises the following components in parts by weight: 1 g of a tallow primary amine corrosion inhibitor, 2 g of citric acid, 15 g of glycerol, 3 g of a sodium dodecyl sulfate surfactant, 25 g of bisphenol A type E51 epoxy resin, and 4 g of modified carbon nanotubes.
[0033] The preparation method of imidazole polyurethane is as follows:
[0034] (1) Add 1 g of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 3.1 g of 2-aminoethanethiol to 70 mL of ethanol, heat to 25 °C and react for 6 h, then add 2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 50 °C for 1 h. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1.
[0035] (2) Add 0.8 g of magnolol to 60 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of intermediate 1 and 0.01 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 35° C. for 2 h, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0036] (3) Add 1 g of 4-hydroxyethylimidazole and 1.1 g of L-lysine to 75 mL of N,N-dimethylformamide solvent, stir and mix, and then add 0.02 g of p-toluenesulfone catalyst, react at 75 °C for 4 h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0037] (4) After removing water from 1.3 g of polyether diol, mix it evenly with 1 g of hexamethylene diisocyanate, introduce nitrogen, then drop 0.01 g of dibutyltin dilaurate catalyst, react at 65 ° C for 2 h to carry out prepolymerization, then add 0.4 g of triazine chain extender and 0.2 g of imidazole chain extender, stir to continue chain extension reaction, react at 50 ° C for 4 h, after the reaction is completed, cool and discharge to obtain imidazole polyurethane.
[0038] The preparation method of modified carbon nanotubes is:
[0039] 2 g of carbon nanotubes were added into a mixed acid solution for acidification, wherein the mixed acid solution was obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 3 g of the acidified carbon nanotubes were added into 60 mL of N,N-dimethylacetamide, and ultrasonically dispersed, and 6 g of an imidazole chain extender, 7 g of acyl chloride silane and 0.4 g of a pyridine catalyst were added thereto, and the mixture was reacted at 60° C. for 9 h. After the reaction, the mixture was centrifuged, washed with acetone, and dried to obtain modified carbon nanotubes.
[0040] The preparation method of the polymer sealing reinforced filler tape is as follows:
[0041] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane into a rubber mixer and mix them evenly. Mix them at -0.05 MPa vacuum and 60°C for 1 hour, and cool them to room temperature naturally to obtain a sealant layer.
[0042] S2. The tallow primary amine corrosion inhibitor, parts of citric acid, glycerol, parts of sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.5h and allowed to stand for 5min to obtain an active surface layer;
[0043] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, having a thickness of 0.9 mm;
[0044] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.4 mm;
[0045] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.3 mm;
[0046] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0047] Example 2
[0048] A polymer sealing and reinforcing filler tape, comprising a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: 60g of butyl rubber, 10g of terpene resin, 5g of low-density polyethylene, 6g of white carbon black, 8g of trieugenol quaternary ammonium salt borate tackifier, 4g of zinc oxide, and 5g of imidazole-based polyurethane;
[0049] The active surface layer comprises the following components in parts by weight: 2 g of a tallow primary amine corrosion inhibitor, 5 g of citric acid, 20 g of glycerol, 8 g of a sodium dodecyl sulfate surfactant, 40 g of bisphenol A type E51 epoxy resin, and 8 g of modified carbon nanotubes.
[0050] The preparation method of imidazole polyurethane is as follows:
[0051] (1) Add 1 g of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 3.6 g of 2-aminoethanethiol to 95 mL of ethanol, heat to 40°C and react for 10 h, then add 2.8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 75°C for 3 h. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1;
[0052] (2) Add 1.1 g of magnolol to 80 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of intermediate 1 and 0.03 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 50° C. for 4 h, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0053] (3) Add 2 g of 4-hydroxyethylimidazole and 2.5 g of L-lysine to 90 mL of N,N-dimethylformamide solvent, stir and mix, and then add 0.06 g of p-toluenesulfone catalyst, react at 90 °C for 7 h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0054] (4) After removing water from 1.5 g of polyether diol, mix it evenly with 1 g of hexamethylene diisocyanate, introduce nitrogen, then drop 0.02 g of dibutyltin dilaurate catalyst, react at 80 ° C for 5 h to carry out prepolymerization, then add 0.5 g of triazine-based chain extender and 0.6 g of imidazole-based chain extender, stir to continue chain extension reaction, react at 70 ° C for 6 h, and after the reaction is completed, cool and discharge to obtain imidazole-based polyurethane.
[0055] The preparation method of modified carbon nanotubes is:
[0056] 5 g of carbon nanotubes were added into a mixed acid solution for acidification, wherein the mixed acid solution was obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 4 g of the acidified carbon nanotubes were added into 90 mL of N,N-dimethylacetamide, and ultrasonically dispersed, and 12 g of an imidazole chain extender, 9 g of acyl chloride silane and 0.6 g of a pyridine catalyst were added thereto, and the mixture was reacted at 80° C. for 11 h. After the reaction, the mixture was centrifuged, washed with acetone, and dried to obtain modified carbon nanotubes.
[0057] The preparation method of the polymer sealing reinforced filler tape is as follows:
[0058] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane into a rubber mixer and mix them evenly. Mix them at -0.1 MPa vacuum and 100 ° C for 1.5 h, and cool them to room temperature naturally to obtain a sealant layer.
[0059] S2. The tallow primary amine corrosion inhibitor, parts of citric acid, glycerol, parts of sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 1 h and allowed to stand for 7 min to obtain an active surface layer;
[0060] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, having a thickness of 1.1 mm;
[0061] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.6 mm;
[0062] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.5 mm;
[0063] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0064] Example 3
[0065] A polymer sealing and reinforcing filler tape, comprising a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: 55g of butyl rubber, 8g of terpene resin, 4g of low-density polyethylene, 5g of white carbon black, 6g of trieugenol quaternary ammonium salt borate tackifier, 3g of zinc oxide, and 4g of imidazole-based polyurethane;
[0066] The active surface layer comprises the following components in parts by weight: 1 g of a tallow primary amine corrosion inhibitor, 3 g of citric acid, 18 g of glycerol, 5 g of a sodium dodecyl sulfate surfactant, 30 g of a bisphenol A type E51 epoxy resin, and 6 g of modified carbon nanotubes.
[0067] The preparation method of imidazole polyurethane is as follows:
[0068] (1) Add 1 g of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 3.5 g of 2-aminoethanethiol to 80 mL of ethanol, heat to 28 °C and react for 8 h, then add 2.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 65 °C for 2 h. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1;
[0069] (2) Add 0.9 g of magnolol to 70 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of intermediate 1 and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 45 ° C for 3 h, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0070] (3) Add 2 g of 4-hydroxyethylimidazole and 2.2 g of L-lysine to 82 mL of N,N-dimethylformamide solvent, stir and mix, and then add 0.04 g of p-toluenesulfone catalyst, react at 85 °C for 6 h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0071] (4) After removing water from 1.4 g of polyether diol, mix it evenly with 1 g of hexamethylene diisocyanate, introduce nitrogen, then drop 0.01 g of dibutyltin dilaurate catalyst, react at 75 ° C for 3 h to carry out prepolymerization, then add 0.45 g of triazine-based chain extender and 0.4 g of imidazole-based chain extender, stir to continue chain extension reaction, react at 60 ° C for 5 h, and after the reaction is completed, cool and discharge to obtain imidazole-based polyurethane.
[0072] The preparation method of modified carbon nanotubes is:
[0073] 4 g of carbon nanotubes were added into a mixed acid solution for acidification, wherein the mixed acid solution was obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 3 g of the acidified carbon nanotubes were added into 80 mL of N,N-dimethylacetamide, and ultrasonically dispersed, and 9 g of an imidazole chain extender, 8 g of acyl chloride silane and 0.5 g of a pyridine catalyst were added thereto, and the mixture was reacted at 70° C. for 10 h. After the reaction, the mixture was centrifuged, washed with acetone, and dried to obtain modified carbon nanotubes.
[0074] The preparation method of the polymer sealing reinforced filler tape is as follows:
[0075] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane to a rubber mixer and mix evenly, mix at -0.1 MPa vacuum conditions and 80°C for 1.2 h, and naturally cool to room temperature to obtain a sealant layer;
[0076] S2. The tallow primary amine corrosion inhibitor, parts of citric acid, glycerol, parts of sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.8h and allowed to stand for 6min to obtain an active surface layer;
[0077] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, having a thickness of 0.9 mm;
[0078] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.5 mm;
[0079] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.4 mm;
[0080] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0081] Example 4
[0082] A polymer sealing and reinforcing filler tape, comprising a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: 45g of butyl rubber, 5g of terpene resin, 3g of low-density polyethylene, 4g of white carbon black, 5g of trieugenol quaternary ammonium salt borate tackifier, 2g of zinc oxide, and 3g of imidazole-based polyurethane;
[0083] The active surface layer comprises the following components in parts by weight: 1 g of a tallow primary amine corrosion inhibitor, 2 g of citric acid, 15 g of glycerol, 3 g of a sodium dodecyl sulfate surfactant, 25 g of bisphenol A type E51 epoxy resin, and 4 g of modified carbon nanotubes.
[0084] The preparation method of imidazole polyurethane is as follows:
[0085] (1) Add 1 g of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 3.6 g of 2-aminoethanethiol to 95 mL of ethanol, heat to 40°C and react for 10 h, then add 2.8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 75°C for 3 h. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1;
[0086] (2) Add 1.1 g of magnolol to 75 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of intermediate 1 and 0.03 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 50° C. for 4 h, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0087] (3) Add 2 g of 4-hydroxyethylimidazole and 2.5 g of L-lysine to 90 mL of N,N-dimethylformamide solvent, stir and mix, and then add 0.06 g of p-toluenesulfone catalyst, react at 90 °C for 4 h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0088] (4) After removing water from 1.5 g of polyether diol, mix it evenly with 1 g of hexamethylene diisocyanate, introduce nitrogen, then drop 0.02 g of dibutyltin dilaurate catalyst, react at 80 ° C for 5 h to carry out prepolymerization, then add 0.5 g of triazine-based chain extender and 0.6 g of imidazole-based chain extender, stir to continue chain extension reaction, react at 70 ° C for 6 h, and after the reaction is completed, cool and discharge to obtain imidazole-based polyurethane.
[0089] The preparation method of modified carbon nanotubes is:
[0090] 5 g of carbon nanotubes were added into a mixed acid solution for acidification, wherein the mixed acid solution was obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 4 g of the acidified carbon nanotubes were added into 75 mL of N,N-dimethylacetamide, and ultrasonically dispersed, and 12 g of an imidazole chain extender, 9 g of acyl chloride silane and 0.6 g of a pyridine catalyst were added thereto, and the mixture was reacted at 80° C. for 11 h. After the reaction, the mixture was centrifuged, washed with acetone, and dried to obtain modified carbon nanotubes.
[0091] The preparation method of the polymer sealing reinforced filler tape is as follows:
[0092] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane to a rubber mixer and mix evenly, mix at -0.1 MPa vacuum conditions and 80°C for 1.2 h, and naturally cool to room temperature to obtain a sealant layer;
[0093] S2. The tallow primary amine corrosion inhibitor, parts of citric acid, glycerol, parts of sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.8h and allowed to stand for 6min to obtain an active surface layer;
[0094] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, having a thickness of 0.9 mm;
[0095] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.5 mm;
[0096] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.4 mm;
[0097] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0098] Example 5
[0099] A polymer sealing and reinforcing filler tape, comprising a sealing adhesive layer and an active surface layer; the sealing adhesive layer is composed of the following components by weight: 60g of butyl rubber, 10g of terpene resin, 5g of low-density polyethylene, 6g of white carbon black, 8g of trieugenol quaternary ammonium salt borate tackifier, 4g of zinc oxide, and 5g of imidazole-based polyurethane;
[0100] The active surface layer comprises the following components in parts by weight: 2 g of a tallow primary amine corrosion inhibitor, 5 g of citric acid, 20 g of glycerol, 8 g of a sodium dodecyl sulfate surfactant, 40 g of bisphenol A type E51 epoxy resin, and 8 g of modified carbon nanotubes.
[0101] The preparation method of imidazole polyurethane is as follows:
[0102] (1) Add 1 g of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 3.5 g of 2-aminoethanethiol to 70 mL of ethanol, heat to 28 °C and react for 8 h, then add 2.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 65 °C for 2 h. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1.
[0103] (2) Add 0.9 g of magnolol to 60 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of intermediate 1 and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 45 ° C for 3 h, centrifuge, wash and dry to obtain a triazine-based chain extender;
[0104] (3) Add 2 g of 4-hydroxyethylimidazole and 2.2 g of L-lysine to 80 mL of N,N-dimethylformamide solvent, stir and mix, and then add 0.04 g of p-toluenesulfonate catalyst, react at 85 °C for 6 h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender;
[0105] (4) After removing water from 1.4 g of polyether diol, mix it evenly with 1 g of hexamethylene diisocyanate, introduce nitrogen, then drop 0.01 g of dibutyltin dilaurate catalyst, react at 75 ° C for 3 h to carry out prepolymerization, then add 0.45 g of triazine-based chain extender and 0.4 g of imidazole-based chain extender, stir to continue chain extension reaction, react at 60 ° C for 5 h, and after the reaction is completed, cool and discharge to obtain imidazole-based polyurethane.
[0106] The preparation method of modified carbon nanotubes is:
[0107] 2 g of carbon nanotubes were added into a mixed acid solution for acidification, wherein the mixed acid solution was obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then 3 g of the acidified carbon nanotubes were added into 60 mL of N,N-dimethylacetamide, and ultrasonically dispersed, and 9 g of an imidazole chain extender, 8 g of acyl chloride silane and 0.5 g of a pyridine catalyst were added thereto, and the mixture was reacted at 70° C. for 10 h. After the reaction, the mixture was centrifuged, washed with acetone, and dried to obtain modified carbon nanotubes.
[0108] The preparation method of the polymer sealing reinforced filler tape is as follows:
[0109] S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane into a rubber mixer and mix them evenly. Mix them at -0.05 MPa vacuum and 60°C for 1 hour, and cool them to room temperature naturally to obtain a sealant layer.
[0110] S2. The tallow primary amine corrosion inhibitor, parts of citric acid, glycerol, parts of sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.5h and allowed to stand for 5min to obtain an active surface layer;
[0111] S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, having a thickness of 0.9 mm;
[0112] S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.4 mm;
[0113] S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.3 mm;
[0114] S6. Through a double-roller machine, the composite is pressed and ground, automatically rolled up after cooling, and cut into pieces to produce a polymer sealing reinforced filler tape.
[0115] Comparative Example 1
[0116] The difference between this comparative example and Example 5 is that polyurethane is used instead of imidazole-based polyurethane.
[0117] Comparative Example 2
[0118] The difference between this comparative example and Example 5 is that carbon nanotubes are used instead of modified carbon nanotubes.
[0119] Comparative Example 3
[0120] The difference between this comparative example and Example 5 is that polyurethane is used instead of imidazole-based polyurethane, and carbon nanotubes are used instead of modified carbon nanotubes.
[0121] The limiting oxygen index of the tape was tested using an oxygen index meter, and the combustion level of the tape was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 1.
[0122] Table 1: Flame retardancy tests.
[0123]
[0124] It can be seen from Table 1 that Examples 1-5 of the present invention have better flame retardant effects than Comparative Examples 1-3.
[0125] Pipette 1 mL of 10 8 CFU / mL of Staphylococcus aureus was added to PBS buffer, and then diluted 10-fold to 10 5 CFU / mL, then add the tape sample (1 cm×1cm×0.2cm), and then culture it in a constant temperature incubator at 37℃ with shaking for 24 h. After culture, add PBS buffer to dilute the bacterial solution 10 times in sequence, and then transfer 0.5 mL of the bacterial solution to the agar medium, and continue to culture it at 37℃ with shaking for 24 h. After culture, count the colonies and count the antibacterial rate.
[0126] Table 2: Antibacterial performance test.
[0127]
[0128] It can be seen from Table 2 that Examples 1-5 of the present invention have better antibacterial effects than Comparative Examples 1-3.
[0129] Test the bonding strength of the sealing strip according to GB / T15254-2014.
[0130] Table 3: Bond strength test.
[0131]
[0132] It can be seen from Table 3 that Examples 1-5 of the present invention have better bonding effects than Comparative Examples 1-3.
[0133] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0134] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A polymer sealing and reinforcing filler tape, characterized in that: It comprises a sealant layer and an active surface layer; the sealant layer is composed of the following components by weight: 45-60 parts by weight of butyl rubber, 5-10 parts by weight of terpene resin, 3-5 parts by weight of low-density polyethylene, 4-6 parts by weight of white carbon black, 5-8 parts by weight of trieugenol quaternary ammonium salt borate tackifier, 2-4 parts by weight of zinc oxide, and 3-5 parts by weight of imidazole polyurethane; The active surface layer comprises the following components in parts by weight: 1-2 parts by weight of a tallow primary amine corrosion inhibitor, 2-5 parts by weight of citric acid, 15-20 parts by weight of glycerol, 3-8 parts by weight of a sodium dodecyl sulfate surfactant, 25-40 parts by weight of a bisphenol A type E51 epoxy resin, and 4-8 parts by weight of modified carbon nanotubes; The preparation method of the imidazole-based polyurethane is: (1) Add 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 2-aminoethanethiol to ethanol, heat to 25-40°C and react for 6-10 hours, then add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 50-75°C for 1-3 hours. After the reaction, cool to room temperature to precipitate a precipitate. Filter the product and recrystallize it with ethanol to obtain intermediate 1; (2) Add magnolol to N,N-dimethylformamide solvent, stir and disperse, then add intermediate 1 and benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 35-50° C. for 2-4 hours, centrifuge, wash and dry to obtain a triazine-based chain extender; (3) Add 4-hydroxyethylimidazole and L-lysine to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfone catalyst, react at 75-90°C for 4-7h, and then distill under reduced pressure, wash and dry to obtain an imidazole chain extender; (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then drop dibutyltin dilaurate as a catalyst, react at 65-80°C for 2-5h to perform prepolymerization, then add triazine-based chain extender and imidazole-based chain extender, stir to continue chain extension reaction, react at 50-70°C for 4-6h, and after the reaction is completed, cool and discharge to obtain imidazole-based polyurethane; The mass ratio of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine, 2-aminoethanethiol, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (1) is 1:3.1-3.6:2.4-2.8; The mass ratio of magnolol, intermediate 1 and benzoin dimethyl ether photoinitiator in (2) is 0.8-1.1:1:0.01-0.03; The mass ratio of 4-hydroxyethylimidazole, L-lysine and p-toluenesulfone catalyst in (3) is 1:1.1-1.25:0.02-0.03; The mass ratio of the polyether diol after dehydration, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, triazine chain extender, and imidazole chain extender in (4) is 1.3-1.5:1:0.01-0.02:0.4-0.5:0.2-0.6; The preparation method of the modified carbon nanotubes comprises the following steps: adding 2-5 g of carbon nanotubes to a mixed acid solution for acidification, wherein the mixed acid solution is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1; then adding 3-4 g of the acidified carbon nanotubes to N,N-dimethylacetamide, performing ultrasonic dispersion, and continuously adding 6-12 g of an imidazole chain extender, 7-9 g of acyl chloride silane and 0.4-0.6 g of a pyridine catalyst thereto, reacting at 60-80° C. for 9-11 h, centrifuging after the reaction, washing with acetone, and drying to obtain the modified carbon nanotubes.
2. A method for preparing the polymer sealing reinforcing filler tape as claimed in claim 1, characterized in that: The preparation method of the polymer sealing and reinforcing filler tape is as follows: S1. Add butyl rubber, terpene resin, low-density polyethylene, white carbon black, trieugenol quaternary ammonium salt borate tackifier, zinc oxide, and imidazole polyurethane into a rubber mixer and mix them evenly. Mix them at a temperature of 60-100°C for 1-1.5 hours under a vacuum condition of -0.05 to -0.1 MPa, and naturally cool to room temperature to obtain a sealant layer. S2. The tallow primary amine corrosion inhibitor, citric acid, glycerol, sodium dodecyl sulfate surfactant, bisphenol A type E51 epoxy resin, and modified carbon nanotubes were mixed and stirred with a powerful electric stirrer at room temperature for 0.5-1h and allowed to stand for 5-7min to obtain an active surface layer; S3. The sealant layer is uniformly extruded by an extruder and coated onto a high-density polyethylene film at the mouth of the molding die, with a thickness of 0.9-1.1 mm; S4. The active surface layer is evenly applied to the surface of the sealant layer with a thickness of 0.4-0.6 mm; S5. The polyethylene terephthalate material is attached to the active surface layer with a thickness of 0.3-0.5 mm; S6. Through a double-roller machine, calendering and compounding, automatic winding after cooling, slitting and forming, a polymer sealing reinforced filler tape is obtained.
Citation Information
Patent Citations
Carbon nanotube modified polyurethane composite material
CN105238034A
Lightweight flexible heat-conducting bondable electromagnetic shielding composite material and preparation method thereof
CN117683475A